Many-body physics with ultracold gases - n; Salomon, C. (Christophe); Shlyapnikov, Georgy V.; Cugliandolo, L. F. (Leticia F.) (Oxford : Oxford University Press, 2013)
This title provides authoritative tutorials on the most recent achievements in the field of quantum gases at the interface between atomic physics and quantum optics, condensed matter physics, nuclear and high-energy physics, non-linear physics and quantum information.
Selected conference papers.
Includes bibliographical references.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Cold gases -- Congresses; Nuclear physics -- Congresses; Condensed matter -- Congresses; Quantum theory -- Congresses